Toward Understanding Phage:Host Interactions in the Rumen; Complete Genome Sequences of Lytic Phages Infecting Rumen Bacteria - Gilbert, Rosalind A.; Kelly, William J.; Altermann, Eric; Leahy, Sinead C.; Minchin, Catherine; Ouwerkerk, Diane; Klieve, Athol V. (Frontiers in Microbiology, 2017)
The rumen is known to harbour dense populations of bacteriophages (phages) predicted to be capable of infecting a diverse range of rumen bacteria. While bacterial genome sequencing projects are revealing the presence of phages which can integrate their DNA into the genome of their host to form stable, lysogenic associations, little is known of the genetics of phages which utilise lytic replication. These phages infect and replicate within the host, culminating in host lysis and the release of progeny phage particles. While lytic phages for rumen bacteria have been previously isolated, their genomes have remained largely uncharacterised. Here we report the first complete genome sequences of lytic phage isolates specifically infecting three genera of rumen bacteria: Bacteroides, Ruminococcus and Streptococcus. All phages were classified within the viral order Caudovirales and include two phage morphotypes, representative of the Siphoviridae and Podoviridae families. The phage genomes displayed modular organisation and conserved viral genes were identified which enabled further classification and determination of closest phage relatives. Co-examination of bacterial host genomes led to the identification of several genes responsible for modulating phage:host interactions, including CRISPR/Cas elements and restriction-modification phage defence systems. These findings provide new genetic information and insights into how lytic phages may interact with bacteria of the rumen microbiome.